HUBUNGAN PENGETAHUAN ORANG TUA DENGAN PERAWATAN LUKA SIRKUMSISI PADA ANAK USIA SEKOLAH 10 – 12 TAHUN - Pasaribu, Dewi Astuti; Sembiring, Elyani; Hutahaean, Martina (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Circumcision (circumcision) is a minor surgical procedure that is generally performed on children. Circumcision is the act of cutting the foreskin on a boy's vital organ, namely the skin that covers the head of the penis. The aim of the study was to determine the relationship between parental knowledge and wound care in school-aged children 10-12 years after circumcision. This type of research is qualitative description with a cross tabulation approach. The total population is all children who underwent circumcision (50 respondents) with samples taken using a random sampling system. From the results of the research in univariate analysis, it was obtained: Frequency distribution of the level of knowledge of the majority of parents in the Sufficient category = 27 (54.0%); Frequency distribution of wound care in school-aged children 10-12 years after circumcision, the majority in the Good care category = 34 (68.0%); Frequency distribution of the relationship between parental knowledge level and wound care in school-aged children 10-12 years after circumcision. The majority of parental knowledge levels are in the Fair category and wound care is in the Good category = 31 (62.0%). The results of the bivariate analysis research show that there is a significant relationship p value = 0.01 < ? = 0.05 (significance value 95%; H0 is rejected and Ha is accepted). It is assumed that "There is a correlation (relationship) between parental knowledge and wound care in school-aged children 10-12 years after circumcision". It is hoped that parents can increase knowledge about injuries in school-aged children 10 - 12 years after undergoing circumcision.